EFEKTIFITAS PENGELOLAAN TERMINAL TRANSPORTASI DARAT - Febri Yuliani, Indra Alpino, Sujianto, (Jurnal Ilmu Administrasi Negara, 2019)
Effectiveness of Management of Land Transportation Terminals. This study aims to find out how the Management of the Indragiri Laksmana Bandar Terminal is carried out by the Transportation Service of Indragiri Hilir Regency. This research is descriptive research. Data collection techniques used are interviews, observation, and literature. The results showed that the Transportation Agency of Indragiri Hilir Regency had 3 important roles, namely the Transportation Service of Indragiri Hilir Regency as a regulator or policy maker, the Transportation Agency as a provider of facilities related to the field of public transportation and the Transportation Agency as supervisors in supervising every policy and infrastructure provided for support the need for transportation services. The results of the study indicate that terminal operations have not been fully implemented based on standard type B terminals.